Prevalence Of Hypertension And Its Impact On Birth Weight And Current Body Weight In School Children In Tehran - Ali Pasha Meysami; Zahra Mokhtari; Nages Tabrizchi; Reza Ganji Mohammad; Zahra Akbari; Sina Moradmand; Seyede Zoha Mirkhani (Tehran University of Medical Sciences, 2012)
Background and Aim: High blood pressure in children, especially in developing countries is growing. Birth weight, age and anthropometric parameters such as current height and weight as factors in childhood hypertension and adolescents have been considered. The objective of this study was to evaluate the prevalence of hypertension in children school and it's correlation with birth weight and current height and weight. Materials and Methods: In a cross-sectional study, between 2006-2008 among 1195924 students in Tehran's schools, 2040 individuals were selected by multistage random sampling method. Inclusion criteria were age 6 to 19 years, physical health and having health card. The twins, students with hypertensive and smoker mothers were excluded. Statistical analysis was conducted by SPSS software version 16. The multiple regression analysis equation was used to determine the predictors of blood pressure levels. Results: 69 students(3.4%), including 4.84% of girls and 3.5% of boys had high blood pressure(p=0.14). Significant direct correlation between age, current weight, current height, and body mass index, systolic and diastolic blood pressure was found. However, birth weight has a weak reverse linear correlation with systolic and diastolic blood pressure(respectively=-0.152 and r=-0.111, p<0.001). Conclusion: Attention to Current size, especially Current weight with consideration to birth weight can be helpful to predict blood pressure in adulthood. This is important in monitoring the weight and blood pressure in children, especially child with an abnormal birth weight and overweight children.